Linking digital leadership and employee digital performance in SMEs in China: The chain-mediating role of high-involvement human resource management practice and employee dynamic capability - Wang, Guifang; Dato Mansor, Zuraina; Leong, Yee Choy (Elsevier, 2024)
Background: In the digital era, the role of digital leadership is becoming increasingly prominent. However, the exploration of the alignment between digital leadership and high-involvement human resource management practices (HI-HRMPs) in influencing employee-based resources remains an overlooked research area among current scholars. Objective: This study aims to analyze the influence of these elements on the digital performance of employees. Based on the Resource-Based View (RBV) and Dynamic Capability Theory (DCT), this research focuses on Chinese Small and Medium Enterprises (SMEs) and employs purposive sampling to select four representative regions in China (Shanghai, Guangzhou, Guizhou, and Anhui). The survey targeted employees within SMEs and was conducted using questionnaire surveys. Structural equation modeling (AMOS) is utilized for analysis. Results: The findings indicate that: (1) digital leadership cannot directly influence employee digital performance and employee dynamic capability but can directly influence HI-HRMP; (2) HI-HRMP mediate the influence of digital leadership on employee digital performance, but employee dynamic capability cannot mediate the influence of digital leadership on employee digital performance; (3) HI-HRMP and employee dynamic capability play a chain mediating role between digital leadership and employee digital performance. Conclusion: In the digital market, digital leadership improves employee digital performance by boosting HI-HRMP and enhancing employee dynamic capabilities. The findings support studies on practical applications and link between digital leadership and employee digital performance. The uniqueness of this study lies in applying HI-HRMP and employee dynamic capabilities as chain mediating variables in the digital market. This approach extends the application of HRMPs and dynamic capability theory, providing theoretical guidance and decision support for the digital operations of SMEs. © 2024 The Authors